KEJAhATAN INTELEKTUAL DALAM PERSFEKTIF kEMERDEKAAN - Rosma Kadir (Universitas Negeri Gorontalo, 2009)
The fundamental nature from independence is freedom by esteeming others independence. Freedom, not as of our eye are free independenced from all kind of colonilisation and discrimination, but value from an independence would for more means if we to let others also can enioy his own freedom, do not disturb it, more than anything else by seizeíts the rights. Independence at conceptual level, analogy as a situationt, where we feel independent,feel secure, and free does something according to our desires, free articulated free holding responsible, so that thereby will not bother independence of others with our freedom